Values of Multicultural Islamic Education at UPT SD Negeri 231 Gresik - Zainudin, Ihsanul Khuluk; Muid, Abdul (JASNA : Journal For Aswaja Studies, 2025)
This study aims to analyze the implementation of multicultural Islamic education values at UPT SD Negeri 231 Gresik, focusing on teaching tolerance, harmony, and equality among students. The research method is descriptive and qualitative, collecting data through observation, interviews, and documentation. The findings show that the teachers at this school implement multicultural values by integrating Islamic teachings, particularly those found in the Qur'an and hadith, into the learning process. Additionally, they employ various methods such as lectures, discussions, question-and-answer sessions, role modeling, and habituation to instill a respectful attitude and harmonious coexistence. Extracurricular activities, such as sports, cultural arts, and Scouts, strengthen multicultural values outside the classroom. However, the study found limitations in using traditional learning media, such as worksheets and textbooks. This study implies that multicultural education should be an integral part of the educational curriculum, especially in shaping students' character to be tolerant and appreciative of diversity and strengthening social harmony in a pluralistic society.